Mitigation of Sexual Harassment Based on The Yellow Book Study in Islamic Boarding Schools - Nur, Muhammad; Najib, Ariz; Wahyuni, Fitri; Rizky Mustikasari, Bella; Silvia Rahayu, Ajeng; Muflihatusyawal, Edfitri (Universitas Pendidikan Indonesia (UPI), 2022)
AbstractOvercoming the moral decline that is currently sweeping the Indonesian nation, Islamic boarding schools have a large role in the world of education. The sad thing is that there are many cases of sexual harassment in educational settings and even in Islamic boarding schools. Whereas pesantren should be an ideal place to form character, not only through intellectual intelligence but also expect emotional and spiritual intelligence so that noble character is realized. This study uses the narrative review approach and aims to identify whether learning the yellow book related to sexual education has implications for mitigating sexual harassment in Islamic boarding schools. The results of the study then showed that the yellow book was able to eradicate the rampant sexual harassment, especially that which occurred in Islamic boarding schools. Therefore, the teachings of the yellow book should be studied, deepened, and implemented in real life, so that sexual harassment in Islamic boarding schools can be minimized or even completely absent. Keywords: sexual harassment, yellow book, Islamic boarding school